2016
DOI: 10.1098/rstb.2015.0089
|View full text |Cite
|
Sign up to set email alerts
|

Negotiation and appeasement can be more effective drivers of sociality than kin selection

Abstract: Two alternative frameworks explain the evolution of cooperation in the face of conflicting interests. Conflicts can be alleviated by kinship, the alignment of interests by virtue of shared genes, or by negotiation strategies, allowing mutually beneficial trading of services or commodities. Although negotiation often occurs in kin-structured populations, the interplay of kin-and negotiation-based mechanisms in the evolution of cooperation remains an unresolved issue. Inspired by the biology of a cooperatively b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 53 publications
2
78
0
Order By: Relevance
“…B 371: 20150090 them, increasing their levels of effort only when the dominants were restored [58,61]. Although these studies do not demonstrate that cheating itself should be selectively favoured (or, indeed, that cheating occurs) under natural conditions, they provide strong behavioural evidence that dominants can, and do, monitor the actions of subordinate group members; and that aggression by dominants can induce cooperation by subordinates [30,[62][63][64].…”
Section: Empirical Evidence For Cheating and Punishment In Cooperativmentioning
confidence: 90%
“…B 371: 20150090 them, increasing their levels of effort only when the dominants were restored [58,61]. Although these studies do not demonstrate that cheating itself should be selectively favoured (or, indeed, that cheating occurs) under natural conditions, they provide strong behavioural evidence that dominants can, and do, monitor the actions of subordinate group members; and that aggression by dominants can induce cooperation by subordinates [30,[62][63][64].…”
Section: Empirical Evidence For Cheating and Punishment In Cooperativmentioning
confidence: 90%
“…Reciprocity, the third potential cause of correlated pay-offs, is arguably the most contended possibility to generate cooperation and altruism [12,32]. It is the theme of this article and a focus of many contributions to this special issue of the Philosophical Transactions [7,[33][34][35][36][37].…”
Section: Correlated Pay-offsmentioning
confidence: 96%
“…Similar phenomena, though the modeling framework is quite different from the current one, were found in the continuous-time, two-player "coaction" model by van Doorn et al (2014), where the authors found that (i) real time coaction in response to partner's behavior (analogous to my negotiation stage) generally favors cooperation but that (ii) once delay in information about the behavior of one's partner is introduced, as is often the case with discrete-round repeated Prisoner's Dilemma games, achieving cooperation becomes more difficult. Therefore, the introduction of a negotiation stage, if the possibility of lying is suppressed by some mechanism such as punishment Quiñones et al, 2016) or ostracism (Nakamaru and Yokoyama, 2014), contributes to enhancing the efficiency of conditional cooperation. It is notable that my model explains the presence of conditional cooperation not as an evolutionarily stable strategy (ESS).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing interest in studying negotiation processes to see how flexibility in behavior shapes an evolutionary outcome (McNamara et al, 1999;McNamara, 2013;Quiñones et al, 2016;Ito et al, 2017). My negotiation model here is such an attempt to reveal the origin of conditional cooperators and to explain why we observe both cooperation and defection in the real world.…”
Section: Discussionmentioning
confidence: 99%